Critical Debates and Developments in Child Protection - Parton, Nigel (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book includes chapters from a range of countries which critically reflect on recent developments in child protection policy and practice. It is a follow-up to 'Contemporary Developments in Child Protection' Volumes 1, 2 and 3, which were published by MDPI in 2015. It begins from the premise that the concerns of child protection have broadened considerably in recent years, and that the policies and practices are complex. It also begins from the recognition that child protection policies and practices are themselves shaped by a wide range of social, cultural and political factors, which vary both over time and in different contexts and jurisdictions.